1995
DOI: 10.1093/carcin/16.10.2583
|View full text |Cite
|
Sign up to set email alerts
|

Albumin adducts, hemoglobin adducts and urinary metabolites in workers exposed to 4,4′-methylenediphenyl diisocyanate

Abstract: 4,4'-Methylenediphenyl diisocyanate (MDI) is the most widely used isocyanate in the manufacture of polyurethanes. MDI has been implicated as one of the major causes of occupational asthma. Hydrolysis of MDI can yield 4,4'-methylenedianiline (MDA), which is a suspected human carcinogen. Thus the need to monitor occupational exposure to MDI is of great significance. The use of air monitors alone has been found to be insufficient and there is a need for sensitive markers of recent and long-term exposure. We obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
2
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 0 publications
3
81
2
1
Order By: Relevance
“…Die Halbwertszeit der TDI-Addukt-Fragmente in Plasma ist deutlich länger und wird mit 10 und 21 Tagen angegeben [Lind et al 1996[Lind et al , 1997. Nach MDI-Belastung wurde eine bis zu vierstündige Halbwertszeit für die Ausscheidung der MDI-Addukt-Fragmente im Urin beschrieben [Schütze et al 1995;Sepai et al 1995]. Die mittlere Halbwertszeit für die HDI-Addukt-Fragmente im Urin beträgt 2,5 h [Brorson et al 1990;Greim 1996;Tinnerberg et al 1995] und für die IPDI-Addukt-Fragmente im Urin 2,8 h [Tinnerberg et al 1995].…”
Section: Zuverlässigkeitskriterien Der Methodeunclassified
“…Die Halbwertszeit der TDI-Addukt-Fragmente in Plasma ist deutlich länger und wird mit 10 und 21 Tagen angegeben [Lind et al 1996[Lind et al , 1997. Nach MDI-Belastung wurde eine bis zu vierstündige Halbwertszeit für die Ausscheidung der MDI-Addukt-Fragmente im Urin beschrieben [Schütze et al 1995;Sepai et al 1995]. Die mittlere Halbwertszeit für die HDI-Addukt-Fragmente im Urin beträgt 2,5 h [Brorson et al 1990;Greim 1996;Tinnerberg et al 1995] und für die IPDI-Addukt-Fragmente im Urin 2,8 h [Tinnerberg et al 1995].…”
Section: Zuverlässigkeitskriterien Der Methodeunclassified
“…Most of the MDI is eliminated as conjugate and with the urine. After hydrolysis of the urine, the MDI conjugates can be detected as MDA (Schütze et al 1995;Sepai et al 1995).…”
Section: Metabolism and Toxicokineticsmentioning
confidence: 99%
“…A very small amount of MDI also binds to hemoglobin, so that MDI-Hb adducts are detectable in the erythrocytes of workers exposed to MDI (Schütze et al 1995;Sepai et al 1995) as well as in those of rats (Pauluhn 2002;Sabbioni et al 2000).…”
Section: Metabolism and Toxicokineticsmentioning
confidence: 99%
“…Incidentally, it is known that TDI can be easily to be hydrolyzed, and changed to toluene diamine (TDA), although Sabbioni et al 11) also concluded that conjugation is the predominant reaction after TDI exposure in rats, and that TDA is not a primary in vivo reaction product under the conditions they tested. In rats, hemoglobin (Hb) adducts were found to correlate with the administered dose of either MDA (4,4'-methylenedianiline) or MDI [11][12][13] .…”
Section: Mechanisms Of Action After Exposurementioning
confidence: 99%